Microfluidic Neural Devices: 3D‐Printed Soft Lithography for Complex Compartmentalized Microfluidic Neural Devices (Adv. Sci. 16/2020). Issue 16 (19th August 2020) - Kajtez, Janko; Buchmann, Sebastian; Vasudevan, Shashank; Birtele, Marcella; Rocchetti, Stefano; Pless, Christian Jonathan; Heiskanen, Arto; Barker, Roger A.; Martínez‐Serrano, Alberto; Parmar, Malin; Lind, Johan Ulrik; Emnéus, Jenny
Abstract : In article number 2001150, Janko Kajtez, Johan Ulrik Lind, and co‐workers present a 3D printing approach to soft lithography for the manufacturing of open‐well compartmentalized microfluidic devices used to engineer human stem‐cell derived neural networks in vitro. The approach provides larger freedom of design, removes the need for manual postprocessing, increases the biocompatibility of the system, and enables fast prototyping at the micro‐ and macroscale.